Central Nervous System Involvement in Pediatric Systemic Autoimmune Diseases - Stanton, Brielle; Knight, Andrea (Journal of Pediatric Neurology, 2018)
Central nervous system (CNS) involvement occurs in many pediatric systemic autoimmune diseases. These manifestations are often associated with increased morbidity and mortality and can have adverse long-term effects on neurodevelopmental, health-related, and quality-of-life outcomes. In this review, we summarize the existing literature on CNS involvement in pediatric systemic autoimmune diseases, compare diagnostic findings, and describe current treatments. CNS manifestations of pediatric systemic autoimmune disease present diagnostic and management challenges due to their relatively rare occurrence in children, the difficulty in confirming direct CNS involvement as opposed to secondary symptoms occurring as a consequence of systemic inflammation, and the need to define treatment strategies effective for CNS involvement.
Keywords: systemic autoimmune disease; pediatric; central nervous system